Cnm of Streptococcus mutans is important for cell surface structure and membrane permeability - Naka, Shuhei; Matsuoka, Daiki; Goto, Kana; Misaki, Taro; Nagasawa, Yasuyuki; Ito, Seigo; Nomura, Ryota; Nakano, Kazuhiko; Matsumoto-Nakano, Michiyo (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus mutans, a Gram-positive facultative anaerobic bacterium, is a major pathogen of dental caries. The protein Cnm of S. mutans is involved in collagen binding, but its other biological functions are unknown. In this study, a Cnm-deficient isogenic mutant and a complementation strain were generated from a Cnm-positive S. mutans strain to help determine the properties of Cnm. Initially, comparison of the cell surface structure was performed by electron microscopy, which demonstrated that Cnm appears to be localized on the cell surface and associated with a protruding cell surface structure. Deep RNA sequencing of the strains revealed that the defect in Cnm caused upregulated expression of many genes related to ABC transporters and cell-surface proteins, while a few genes were downregulated. The amount of biofilm formed by the Cnm-defective strain increased compared with the parental and complemented strains, but the biofilm structure was thinner because of elevated expression of genes encoding glucan synthesis enzymes, leading to increased production of extracellular polysaccharides. Particular antibiotics, including bacitracin and chloramphenicol, had a lower minimum inhibitory concentration for the Cnm-defective strain than particular antibiotics, including bacitracin and chloramphenicol, compared with the parental and complemented strains. Our results suggest that S. mutans Cnm is located on the cell surface, gives rise to the observed protruding cell surface, and is associated with several biological properties related to membrane permeability.